Potential Anticancer Properties and Mechanisms of Action of Formononetin. (28th July 2019) - Jiang, Dongjun; Rasul, Azhar; Batool, Rabia; Sarfraz, Iqra; Hussain, Ghulam; Mateen Tahir, Muhammad; Qin, Tian; Selamoglu, Zeliha; Ali, Muhammad; Li, Jiang; Li, Xiaomeng
Abstract : Nature, a vast reservoir of pharmacologically active molecules, has been most promising source of drug leads for the cure of various pathological conditions. Formononetin is one of the bioactive isoflavones isolated from different plants mainly from Trifolium pratense, Glycine max, Sophora flavescens, Pycnanthus angolensis, and Astragalus membranaceus . Formononetin has been well-documented for its anti-inflammatory, anticancer, and antioxidant properties. Recently anticancer activity of formononetin is widely studied. This review aims to highlight the pharmacological potential of formononetin, thus providing an insight of its status in cancer therapeutics. Formononetin fights progression of cancer via inducing apoptosis, arresting cell cycle, and halting metastasis via targeting various pathways which are generally modulated in several cancers. Although reported data acclaims various biological properties of formononetin, further experimentation on mechanism of its action, medicinal chemistry studies, and preclinical investigations are surely needed to figure out full array of its pharmacological and biological potential.